Mangrove Ecosystems of Asia [electronic resource] : Status, Challenges and Management Strategies - Faridah-Hanum, I.; Latiff, A.; Hakeem, Khalid Rehman; Ozturk, Munir; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
Mangrove ecosystems occur in the inter-tidal region between sea and land in tropical and sub-tropical latitudes and provide important ecosystem goods and services. These forests help stabilize shorelines and reduce the devastating impact of natural disasters such as tsunamis and hurricanes. They serve as breeding and nursing grounds for marine species, and are sources of food, medicine, fuel, and building materials for local communities. However, these ecosystems have been declining at an alarming rate?perhaps even more rapidly than inland tropical forests?and much of what remains is in a degraded condition. Habitat destruction through human encroachment has been the primary cause of mangrove loss. The loss of mangrove habitats has resulted in a decline in fishery resources and biodiversity. This book provides an up-to-date account of mangrove ecosystems in Asia as well as restoration and ecosystem management techniques to ensure the sustainability and conservation of the mangrove. The book is divided into sections presenting the distribution and status of mangrove ecosystems in Asia, the challenges they are facing, the issues and opportunities arising from these challenges, and management strategies for mangrove conservation.
Chapter 1: Mangrove Ecosystems of Malaysia: Status, Challenges and Management Strategies -- Chapter 2: Distribution and Rarity of Rhizophoraceae in Peninsular Malaysia -- Chapter 3: Distribution and Current Status of Mangrove Forests in Indonesia -- Chapter 4: Mangrove Forests in Thailand -- Chapter 5: Philippines' Mangrove Ecosystem: Status, Threats and Conservation -- Chapter 6: Distribution, Characteristics and Economic Importance of Mangrove Forests in Iran -- Chapter 7: Plant Diversity and Forest Structure of the Three Protected Areas (Wildlife Sanctuaries) of Bangladesh Sundarbans: Current Status and Management Strategies -- Chapter 8: Mangrove Fauna of Asia -- Chapter 9: Mangrove Forests of Timor-Leste: Ecology, Degradation, and Vulnerability to Climate Change -- Chapter 10: Vulnerability of Mangroves to Climate Change -- Chapter 11: Impacts of Climate Change on Asian Mangrove Forests -- Chapter 12: Quantification of Soil Organic Carbon Storage and Turnover in Two Mangrove Forests Using Dual Carbon Isotopic Measurements -- Chapter 13: The Relationship between Mangrove Deforestation and Economic Development in Thailand -- Chapter 14: Remote Sensing Technology: Recent Advancements for Mangrove Ecosystems -- Chapter 15: Management Strategies for Sustainable Exploitation of Aquatic Resources of the Sundarbans Mangrove, Bangladesh -- Chapter 16: Economic Sustainability for Halophyte Cash Farms in Urban Environments -- Chapter 17: Research and Development Activities towards Sustainable Management of Mangroves in Peninsular Malaysia -- Chapter 18: Climate Change Adaptation: Management Options for Mangrove Areas -- Chapter 19: Managing Mangrove Habitat Expansion in New Zealand -- Chapter 20: Mangroves are Wetlands, not Forests: Some Implications for their Management.
Keywords: Life sciences; Ecosystems; Forestry